2008
DOI: 10.1063/1.2957073
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of SrFeO3/Al2O3 thin films: Transmission electron microscopy study and conductometric sensing response

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Complex transition-metal oxides have attracted considerable attention of research due to their electrical, magnetic, and optical properties, which can be used for the development of various new concept devices, such as energy harvest, electrical, and chemical sensors, etc. Perovskite cobaltates exhibit remarkable mixed conductivity and catalytic properties at high temperature as well as interesting magnetic and electrical transport properties at low temperature. Among them, the oxygen-deficient double perovskite cobaltates LnBa­Co 2 O 5.5+δ (Ln = Lanthanide) show particularly interesting phenomena of the order–disorder at the A-cation sites in the cobaltate system. Especially, the very small difference in the A-site cations’ radii between La 3+ and Ba 2+ in the LaBa­Co 2 O 5.5+δ (LBCO) can form complex A-site order, nanoarea order, and disorder layered perovskite structures and induce various exciting physical phenomena, such as various oxidation states (Co 2+ /​Co 3+ /Co 4+ ) of cobalt, different spin state configurations, giant MR effect, metal insulator transition, etc. In order to fully understand the magnetic and transport properties of such complex cobalt oxides, the single crystalline samples are critically desired. In our previous work, we have fabricated highly epitaxial single crystalline LBCO thin films on (001) LaAlO 3 , , (001) SrTiO 3 , , and (001) MgO and found that these films possess an extraordinary sensitivity to reducing/oxidizing environments and an exceedingly fast redox reaction at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Complex transition-metal oxides have attracted considerable attention of research due to their electrical, magnetic, and optical properties, which can be used for the development of various new concept devices, such as energy harvest, electrical, and chemical sensors, etc. Perovskite cobaltates exhibit remarkable mixed conductivity and catalytic properties at high temperature as well as interesting magnetic and electrical transport properties at low temperature. Among them, the oxygen-deficient double perovskite cobaltates LnBa­Co 2 O 5.5+δ (Ln = Lanthanide) show particularly interesting phenomena of the order–disorder at the A-cation sites in the cobaltate system. Especially, the very small difference in the A-site cations’ radii between La 3+ and Ba 2+ in the LaBa­Co 2 O 5.5+δ (LBCO) can form complex A-site order, nanoarea order, and disorder layered perovskite structures and induce various exciting physical phenomena, such as various oxidation states (Co 2+ /​Co 3+ /Co 4+ ) of cobalt, different spin state configurations, giant MR effect, metal insulator transition, etc. In order to fully understand the magnetic and transport properties of such complex cobalt oxides, the single crystalline samples are critically desired. In our previous work, we have fabricated highly epitaxial single crystalline LBCO thin films on (001) LaAlO 3 , , (001) SrTiO 3 , , and (001) MgO and found that these films possess an extraordinary sensitivity to reducing/oxidizing environments and an exceedingly fast redox reaction at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed ionic/electronic conducting materials are of increasing interest owing to their potential applications in various novel devices such as ceramic membranes, ultra sensitive chemical sensor, partial oxidation reactors as well as electrodes in solid oxide fuel cell (SOFC). To improve the performance of those devices, the mixed ionic electronic conducting materials should meet the requirements of both high oxygen diffusivity and great enhancement of surface exchange rate, , These two desirable attributes are typically found in the oxygen deficient doped perovskite cobaltates (Re,A)Co 2 O 5+δ , where Re is a rare earth element and A is an alkaline earth element. The A-site cation average valence favors a compensating population of oxygen vacancies at low oxygen partial pressures and therefore leads to the observed high ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the remarkable mixed conductivity and catalytic properties at high temperature and exciting magnetic and electrical transport properties at low temperature have been intensively studied by scientists and technicians89. All these excellent physical properties have encouraged people to design lots of kinds of functional devices, including solid oxide fuel cells, energy harvest devices, electrical and chemical sensors, etc10111213.…”
mentioning
confidence: 99%